Trust in Online Shopping Among Generation Z: An Analysis of Key Influencing Factors - Hui Ling Lim; Tek Yew Lew; Leon Rong Dat Leow; Zi Ying Lee; Jiayi Li; Yuan Li; Gaurav Sharma; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
The rise of digital platforms has fundamentally transformed consumer behavior, especially among Generation Z (Gen Z), a cohort deeply immersed in the digital age. This study aims to investigate the factors influencing Gen Z's trust in online shopping by examining the relationships between convenience, ease of comparison, product variety, pricing and discounts, security, and environmental concerns. A quantitative method was employed, gathering data from 250 Gen Z participants, with IBM SPSS used to test the proposed hypotheses. The results reveal that pricing and discounts, security, and environmental factors significantly impact Gen Z’s trust in online shopping, while convenience, ease of comparison, and product variety show no significant influence. This research contributes to the understanding of Gen Z's online behavior, highlighting the growing importance of sustainability and secure transactions in fostering trust. The findings offer practical insights for businesses aiming to build stronger relationships with Gen Z, emphasizing the need to focus on ethical practices, competitive pricing, and enhanced security. These insights have implications for both marketers and policymakers in the evolving e-commerce landscape.